جريمة الامتناع عن تسليم قاصر مخالفة لحكم قضائي على ضوء المادة 328 من قانون العقوبات الجزائري - رواحنة, نادية (جامعة الوادي University of Eloued, 2019)
ملخص: يعد الطلاق في الإسلام أبغض الحلال إلى الله لما يترتب عنه من آثار سلبية ونتائج وخيمة، خصوصا بالنسبة للأبناء فرغم مراعاة مصلحتهم في الحكم القاضي بإسناد حضانتهم لمستحقيها، إلا أنه كثيرا ما تقع مخالفة تلك الأحكام القضائية خاصة من طرف الوالدين المنفصلين، وذلك بامتناع أحدهم عن تسليم الطفل إلى من له الحق في حضانته انتقاما منه. هذا الواقع فرض على المشرع الإقرار بحماية جزائية للمحضون، وذلك حتى في مواجهة والديه وأقاربه حين يمتنع أحدهم عن تسليمه لمن حكم له بحضانته، ومن أجل ذلك أورد جريمة الامتناع عن تسليم قاصر مخالفة لحكم قضائي، تدعيما لمبدأ حماية مصلحة المحضون من جهة، وضمانا لاحترام الأحكام القضائية من جهة أخرى، وهذا المقال يوضح كيف عالج المشرع هذه الجريمة على ضوء المادة 328 من قانون العقوبات. Abstract: Divorce in Islam is an abomination due to the devastating repercussions it has, particularly on children. Although the court ruling entrust their custody to the worthy persons, it is often violated by parents who abstain from extraditing the child to the eligible party for the custody as a sort of revenge. By virtue of what preceeds, the Algerian legislator has granted a criminal protection to the child subject to custody, even in the face of his parents and relatives, when one of them refuses to extradite him to a custodian. For this reason, the crime of refusing to extradite a minor contravenes a court order, which reinforces the principle of protecting the interests of the child subject to custody on one hand, and ensures the respect of court orders on another hand. This article explains how the legislator dealt with this crime in light of Article 328 of the Penal Code.
-the Crime Of Refusing To Extradite A Minor As A Contravention To A Court Order In Light Of Article 328 Of The Algerian Penal Code.
Keywords: الامتناع عن تسليم قاصر؛ مخالفة حكم قضائي؛ الحضانة؛ المحضون؛ حق الزيارة؛ الحماية الجزائية; Abstaining from extraditing minor; Violating a court ruling; custody; child subject to custody; visiting right; criminal protection.